La plateforme Moodle et l’évaluation entre pairs dans la didactique de la traduction - Mirella Piacentini (MediAzioni)
The present study focuses on an experience in collaborative, literary translation, supported by the activities and resources of the Moodle online learning platform. The experience was carried out during the Covid-19 pandemic. Although the pandemic may well have encouraged the use of learning platforms, the experience illustrated in the study shows that Moodle offered activities and resources which proved effective in training courses in collaborative literary translation. The proactive pedagogical approach adopted in the study posits translation as a contextualized and interactional cognitive activity and advocates a transition towards authentically transformational approaches in the training of translators (Kiraly, 2000).